Continuation of air services at Berlin-Tegel and its effects on rental prices - Philipp Breidenbach; Jeffrey P. Cohen; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2019)
Berlin-Brandenburg airport (BER) has become well-known far beyond German borders due to substantial mis-planning and heavy delays in opening. Planned to open in March 2012 and to take over all air-transport services from Germany's capital city, with the other airports expected to close, construction work at BER is still ongoing in 2019. Four weeks before the expected opening of the airport, the opening was suddenly delayed by several months. This unexpected delay was an exogeneous shock for residents surrounding the largest existing airport, Berlin-Tegel, which is expected to close upon the opening of Berlin-Brandenburg. A series of additional delay announcements followed. We analyze the effect of airport noise and proximity to the airport on housing rental prices. Our identification strategy is based on the expectations regarding the closing of Berlin-Tegel airport. The results suggest that there is a negative effect of noise on housing rental prices while there are positive effects of proximity to Berlin-Tegel. These delays reduce rental prices by a small amount, when compared with the noise discounts in the literature for owner-occupied properties in studies of other cities. These findings likely occur because renters have a relatively short time horizon for their tenure in an apartment, on average, to benefit from the future noise reduction. For instance, a one-year delay for a renter who plans to stay in an apartment for only one or two years implies a very low benefit from the future noise reduction. We also find that the benefits from a delay announcement have a net negative effect on prices for rental properties that are in the noisier areas but further drive time from Tegel; and a net positive effect in the less noisy areas that are shorter drive time from Tegel. This likely re flects the disamenity from prolonged airport noise exposure, as well as the benefits from proximity due to expectation of continued ease of employment and travel access. – – Aufgrund der zahlreichen Bauverzögerungen und Baumängel hat der Flughafen Berlin-Brandenburg internationale Bekanntheit erlangt. Mehrere Eröffnungstermine konnten nicht gehalten werden und es kam im Verlauf immer wieder zu nicht erwarteten Verschiebungen der Eröffnungstermine. Diese Verschiebungen haben essenzielle Auswirkungen auf Bewohner, die um den aktuell genutzten Flughafen Berlin-Tegel wohnen, da dieser mit der Eröffnung von BER geschlossen werden soll. Die Bewohner um Tegel sind durch die Verzögerungen (unterwartet) weiterhin den Vor- und Nachteilen der Nähe zum Flughafen ausgesetzt. Sie profitieren einerseits durch Arbeitsplätze und bessere Erreichbarkeit, aber leiden andererseits unter der Lärmbelastung. Durch das einmalige Setup der unerwarteten und kurzfristigen Verlängerung des Betriebs in Tegel ist es uns möglich, die (negativen) Lärmeffekte und (positiven) Erreichbarkeitseffekte kausal zu analysieren. Messgröße ist dabei die Entwicklung von individuellen Mieten, die den Wert der Wohnumgebung bestmöglich abbilden. Dabei können wir beide Effekte (Lärm und Erreichbarkeit) individuell identifizieren. In einer umfassenden Schätzung zeigen wir, dass der negative Lärmeffekt dem positiven Erreichbarkeitseffekt überwiegt.
Keywords: R3; R4; 330; real estate prices; airports; aviation noise; proximity; Germany